LEARNING IN THE COVID ERA AND THE CHANGES IN TEACHING AND LEARNING METHODS AT MTS NII MEDAN - Juliani Juliani; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
This research is entitled Learning in the Covid Era and the Changes in Teaching and Learning Methods at MTs NII Medan ". The problem with the learning system at MTs NII was initially face-to-face learning, but after the news of the Covid pandemic, the learning system was changed to online using certain applications, making it difficult for students to learn online. and we all know that not all students have gadgets / cellphones to study online, they are said to have certain applications that are rarely used by some schools. However, there is a little relief for students who do not have cellphones to be able to go to school if subject teachers are present, so study as usual or call it face-to-face. however, stay safe with health protocols. However, if the teacher of the subject that will take place is not present, the learning is still online, which only distinguishes the place between home and school. This research uses a descriptive qualitative approach. With this research method, it is hoped that it can provide maximum changes in the learning system in the new normal period.Keywords: changes, online learning, pandemic